The Development of Portfolio Evaluation Tools to Improve Expository Writing Skills - Rahayu Kuswardani; Fithriyah Inda Nur Abida; Oikurema Purwati; Nur Fauzia; Diana Budi Darma; Fahri Fahri; Nur Chakim; Muh Aries Hilmi (Hasanuddin University, 2022)
This research is intended to help English teachers both at the college and high school levels in using portfolios as an evaluation tool in writing skills. Portfolio assessment was chosen in this research because of its wide use and easy adaptation to various needs. This study used Research and Development method. The development stage is based on the IQF curriculum implemented in English Language and Literature Department, Universitas Negeri Surabaya. The exploratory writing skills held for students are expected to help them in further writing, namely Thesis Proposal Writing and Academic Journal Writing where students will write down their thoughts about a concept or phenomenon and present an explanation accompanied by adequate research data. The results of the study show that the use of portfolio is quite positive. There is an improvement in students’ writing after applying a portfolio as an evaluation tool for writing skills. However, some additions need to be made to improve the quality and format of the portfolio as an evaluation tool for writing skills.